EFFICIENCY OF INCLUSION OF BIRD,S-FOOT TREFOIL (LOTUS CORNICULATUS L.) IN PASTURABLE HERBAGES ON THE IRRIGATED SITE OF THE FOOTHILL ZONE OF THE SOUTHEAST OF KAZAKHSTAN - K. Aubakirov; K. Zholamanov; K. Erzhanova; R. Neugschwandtner (Scientific Journal of Pedagogy and Economics, 2019)
Results of researches of pasturable use of various bean and cereals grass mixture with participation of bird,s-foot trefoil are given in article (Lotus corniculatus L.) in the conditions of irrigation of a foothill zone of the southeast of Kazakhstan. Inclusion in structure of a grass mixture of bird,s-foot trefoil increases productive longevity of pasturable herbage and preservation as a part of the pasturable mass of bean herbs. The productivity of pasturable weight during 6 years’ use by herbage fluctuates within 256.2-467.1 c/hectare and contents bean in structure at the level of 28.7-30.5%. For the fifth and sixth years the share bean in the mass of a harvest was formed at the expense of bird,s-foot trefoil. In structure of a harvest from third year of use there is a decrease in a share of a lucerne and a cock’s head and increase in a share of bird,s-foot trefoil. This bean grass proved to be as perspective for creation of long cultural pastures on irrigation. At cultivation of bean and cereals grass mixture the structure of the soil significantly improves.